Evaluation Of Usability Level and User Satisfaction of The Licoworks Web-based Ticketing System Using The PSSUQ (Post-study System Usability Questionnaire) Method - I Wayan Wahyu Ivan Mahendra Jaya; Henry Dedy Doken; I Wayan Mahendra Widiatama; Gede Rasben Dantes; Gede Indrawan; I Made Agus Oka Gunawan (INSERT : Information System and Emerging Technology Journal, 2026)
This research aims to evaluate the usability and user satisfaction of the Licoworks web-based ticketing system using the Post-Study System Usability Questionnaire (PSSUQ). The study uses a quantitative descriptive method with 67 active users to see their experience related to system usability, information quality, and interface quality. Data were collected using the 16-item PSSUQ instrument to measure user perceptions. The findings show that Licoworks gets good usability results, with average dimension scores of 2.48–2.49, which are lower than the normative benchmark (μ = 2.82). The system also receives high ratings for information accessibility (Q10: M = 2.42) and ease of use (Q1–Q2: M = 2.46). However, some aspects still need improvement, such as error recovery (Q8: M = 2.49), error messages (Q7: M = 2.51), task completion speed (Q3: M = 2.52), and user orientation (Q5: M = 2.52). Overall, the research concludes that Licoworks provides a satisfying platform for handling support tickets, but regular evaluation is suggested to maintain and improve the user experience.